Smith Wigglesworth : apostle of faith - Frodsham, Stanley Howard, 1882-1969 (Springfield, Mo. : My Healthy Church, 2014)
This inspiring life story tells of Smith Wigglesworth's early years and his struggle with his faith in God. Details his recommitment to God, his ministry with his wife, his search for the Baptism of the Holy Spirit, and how he became God's tool for an incredible, world-renowned healing ministry.
Title from PDF title page (viewed on Aug. 14, 2014).
Keywords: Wigglesworth, Smith, -- 1859-1947.; Evangelists -- England -- Biography; Pentecostals -- England -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Christianity / Denominations; Electronic books